2017
DOI: 10.7575/aiac.ijels.v.5n.3p.16
|View full text |Cite
|
Sign up to set email alerts
|

Arab ESL Secondary School Students’ Spelling Errors

Abstract: English spelling has always been described by many language researchers and teachers as a daunting task especially for learners whose first language is not English. Accordingly, Arab ESL learners commit serious errors when they spell out English words. The primary objective of this paper is to determine the types as well as the causes of spelling errors made by Arab ESL secondary school students. In order to collect the data, a fifty-word standardised spelling test was administered to seventy Arab student part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 11 publications
3
18
0
Order By: Relevance
“…The least type of errors found in the data the students made was the transposition spelling errors (7.78%). The study supported many studies in the literature which found that omission and substitution errors were high compared to other categories of spelling errors as in (Al-Hassan, 2006;Al-Jabri, 2006;Al-Harrasi, 2012;Alhaysony, 2012;Alhaisoni, Al-Zuoud, and Gaudel, 2015;Albalawi, 2016;Al-Sobhi, et,al, 2017;Othoman, 2018;Atatsi, and Amoakohene, 2019). The most common omission errors were dropping the vowel letter [-e] at the end of words as in *college or for 'college' or substitution errors of vowels, as [a] in the place of [u] and [o]as in *camplet for 'complete'.…”
Section: Resultssupporting
confidence: 87%
“…The least type of errors found in the data the students made was the transposition spelling errors (7.78%). The study supported many studies in the literature which found that omission and substitution errors were high compared to other categories of spelling errors as in (Al-Hassan, 2006;Al-Jabri, 2006;Al-Harrasi, 2012;Alhaysony, 2012;Alhaisoni, Al-Zuoud, and Gaudel, 2015;Albalawi, 2016;Al-Sobhi, et,al, 2017;Othoman, 2018;Atatsi, and Amoakohene, 2019). The most common omission errors were dropping the vowel letter [-e] at the end of words as in *college or for 'college' or substitution errors of vowels, as [a] in the place of [u] and [o]as in *camplet for 'complete'.…”
Section: Resultssupporting
confidence: 87%
“…Learning English can be particularly challenging for native Arabic speakers due to pronunciation and orthographic differences. Previous studies agree that the causes of spelling errors tend to be related to interference from the native language in areas where it differs from the second or foreign language (e.g., Ahmed, 2017;Al-Sobhi, Rashid, Abdullah, & Darmi, 2017). This study confirms the findings of the existing studies and at the same time, puts forth another factor, which is the nature of classroom instruction and teachers education.…”
Section: Discussionsupporting
confidence: 88%
“…Several studies have discussed this problem and traced the causes of it (see e.g., Abu-Rabia & Taha, 2006;Al-bereiki, 2016;Al-Busaidi & Al-Saqqaf, 2015;Al-sobhi, Rashid, Abdullah, & Darmi, 2017;Sawalmeh, 2013;Trimasse, 2016). Those authors have considered English spelling a daunting and a difficult skill, particularly to learners whose first language is not English, such as Arab students of English.…”
Section: Why English Spelling Is Difficult For Arab Learners?mentioning
confidence: 99%
“…On the other hand, the lack of connection or a close similarity between English graphemes and phonemes makes the English writing system more difficult. As a result, the English writing system tends to create difficulties for Arab students and consequently most of these learners fail to spell out English words correctly (Al-sobhi et al, 2017). Fender (2008) (EAP).…”
Section: Why English Spelling Is Difficult For Arab Learners?mentioning
confidence: 99%